2022
DOI: 10.1186/s12917-022-03409-y
|View full text |Cite
|
Sign up to set email alerts
|

Heart inflammation and piscine orthoreovirus genotype-1 in Pacific Canada Atlantic salmon net-pen farms: 2016–2019

Abstract: Piscine orthoreovirus genotype-1 (PRV-1) is a virus commonly associated with Atlantic salmon aquaculture with global variability in prevalence and association with disease. From August 2016 to November 2019, 2,070 fish sampled at 64 Atlantic salmon net-pen farm sites during 302 sampling events from British Columbia, Canada, were screened for PRV-1 using real-time qPCR. Nearly all populations became PRV-1 positive within one year of seawater entry irrespective of location, time of stocking, or producer. Cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It therefore does not appear that freshwater Atlantic salmon facilities used to seed regional seawater net-pens have played a meaningful role in PRV-1 persistence in the region in recent years even though they may have acted as a reservoir historically within the region. Further, given that some Atlantic salmon producers rely on PRV-1 infected broodstock for gametes (Polinski et al 2022), it also appears that current iodine-based disinfection strategies employed by the industry are effective at deterring egg-associated transmission of PRV-1 as previously suggested (Polinski et al 2020).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…It therefore does not appear that freshwater Atlantic salmon facilities used to seed regional seawater net-pens have played a meaningful role in PRV-1 persistence in the region in recent years even though they may have acted as a reservoir historically within the region. Further, given that some Atlantic salmon producers rely on PRV-1 infected broodstock for gametes (Polinski et al 2022), it also appears that current iodine-based disinfection strategies employed by the industry are effective at deterring egg-associated transmission of PRV-1 as previously suggested (Polinski et al 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Sixty fish were targeted in each instance to ensure 95% confidence in identifying at least 5% prevalence of PRV at the population level using the USDA APHIS animal sample size calculator (https://www.aphis.usda.gov) assuming 95% diagnostic test sensitivity based on performance of similar qPCR assays (Polinski et al 2021a;Yang et al 2022;Delphino et al 2023). Fish were sampled from the general population at all locations as neither morbidity nor outward visual appearance/behavior have shown correlation with PRV infection prevalence or load (Takano et al 2016;Wessel et al 2017;Polinski et al 2019Polinski et al , 2022Marty et al 2020). Samples were collected at all 12 licensed commercial freshwater salmon facilities in British Columbia: 9 that exclusively rear Atlantic salmon and 3 that exclusively rear Chinook salmon (Supplemental material 1).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we would have had difficulty choosing a salmon virus with a more supportive literature for low virulence than the PRV isolate we used. Specifically, our PRV isolate (i) has not been known to cause disease in sockeye salmon even under circumstances of persistent high-load systemic infection, host saltwater adaptation, or viral co-infection [ 3 , 8 ], (ii) has failed to cause disease in at least 4 other related salmon species in multiple saltwater and freshwater challenge trials conducted in the region [ 9 12 ], (iii) has shown minimal association (< 0.3%) and lack of direct causation for morbidity or mortality in commercial Atlantic salmon net-pen production in its endemic region [ 11 , 13 ], (iv) is considered of low virulence to Norwegian Atlantic salmon and less impactful relative to endemic PRV in that region [ 14 ], and (v) has failed to induce respiratory consequences in Atlantic salmon [ 10 ] similar to what we identified in Sockeye. In consideration of cumulative evidence and literature, a formal risk assessment commissioned by the government of Canada has further concluded the risks posed to wild sockeye salmon from regionally endemic PRV used in our study to be less than minimal [ 15 ].…”
mentioning
confidence: 99%